Craniofacial cavernous hemangioma - Dourmishev, Lyubomir (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2005)
Systemic corticosteroid treatment is reported as effective for problematic cutaneous hemangiomas occuring in infancy, and depend on the dose, the duration of treatment, and the age at which the course of drugs is initiated. A 7-month-old female infant with extended cavernous hemangioma on the left part of forehead, face, and neck which appeared 15 days after birth is presented. She was successfully treated with oral methylprednisolone (initial doses of 3 mg/kg/daily and reduced in steps over 6 months) with significant involution of the lesions and with good aesthetic results. The oral corticosteroid treatment is an efficient medical therapy for common extended cavernous infantile hemangiomas with accelerated growth if initiated early in the proliferative phase.
Keywords: baby; dermatologija; Dojenček; dojenčki; Drug Therapy; Glava in vrat, novotvorbe; Head And Neck Neoplasms; Hemangiom kavernozni; Hemangioma, Cavernous; hemangiomi; Infant; Methylprednisolone; Metilprednizolon; therapy; zdravljenje